Benin : Ex Post Assessment of Performance Under Fund-Supported Programs. (IMF Staff Country Reports; Country Report ;, 2004)
This Ex Post Assessment reviews Benin's progress in implementing economic policies and reforms supported by the Enhanced Structural Adjustment Facility (ESAF) and Poverty Reduction and Growth Facility (PRGF) arrangements since 1993, and draws lessons for a possible successor arrangement. The paper briefly presents developments prior to these arrangements, including the comprehensive stabilization and liberalization of the economy starting in 1989. It also reviews the performance under the three arrangements during 1993-2003. It also discusses the role that the IMF could play in helping the authorities meet various challenges.